2021
DOI: 10.3390/cancers13133162
|View full text |Cite
|
Sign up to set email alerts
|

Modern Diagnosis of Early Esophageal Cancer: From Blood Biomarkers to Advanced Endoscopy and Artificial Intelligence

Abstract: Esophageal cancer (EC) is the seventh most common cancer and the sixth cause of cancer death worldwide. Histologically, esophageal squamous cell carcinoma (ESCC) and esophageal adenocarcinoma (EAC) account for up to 90% and 20% of all ECs, respectively. Clinical symptoms such as dysphagia, odynophagia, and bolus impaction occur late in the natural history of the disease, and the diagnosis is often delayed. The prognosis of ESCC and EAC is poor in advanced stages, being survival rates less than 20% at five year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 90 publications
1
51
0
1
Order By: Relevance
“…Unlike western countries, in China, 90% is ESCC. 3 The pathophysiology of esophageal cancer is a multi‐factor process characterized by multigene involvement and mutation and multi‐stage evolution. 4 Carcinogenesis results from the long‐term combination of environmental and genetic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike western countries, in China, 90% is ESCC. 3 The pathophysiology of esophageal cancer is a multi‐factor process characterized by multigene involvement and mutation and multi‐stage evolution. 4 Carcinogenesis results from the long‐term combination of environmental and genetic factors.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] The identification of new biomarkers for good prognostic stratification and prediction of therapeutic outcomes for esophageal cancer is desperately needed in the clinical setting. [16][17][18] In particular, simple blood-based biomarkers derived from complete blood count, are readily available and inexpensive markers that can reflect the host immune system. 19 The pan-immune-inflammation value (PIV) is a recently proposed scoring system that includes all immune-inflammatory cells in the peripheral blood count (neutrophil count × platelet count × monocyte count)/lymphocyte count).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the metallo endopeptidase activity, several other molecular functions, including chemokine activity, transcriptional activator activity, translation regulatory activity, were included in this study. Previous studies reported similar KEGG pathways linked to the ESCC occurrence [ 3 , 13 , 30 ].…”
Section: Discussionmentioning
confidence: 58%